The effect of COVID-19 in a newly established burn center. Issue 3 (July 2021) - Dayı, Sabriye; Beyeç, Selma; Alpağat, Şeyhmus
Highlights: The effects of COVID-19 on a newly established burn center were investigated. There was no significant difference in the number of patient admissions, age and sex of the patients, burn agent, and length of hospital stay before and after the COVID-19 outbreak. The burn center can work safely in the COVID-19 outbreak, paying a special attention to the precautions mandated by the national and global health authorities. Abstract: Objective: This study aims to investigate the effects of COVID-19 on epidemiological features, burn agent, burn percentage, and hospitalization time in a burn center. Methods: This single-center, retrospective study included a total of 401 patients admitted to our study center between October 2019 and July 2020. The patients who were admitted before March 1, 2020, were considered the pre-March group, and those who were admitted after March 1, 2020, were considered the post-March group. According to their age, the patients were further divided into groups as those aged ≤ 18 years and those aged > 18 years. Demographic and clinical characteristics of patients, burn agent, burn surface area, COVID-19 status, and treatment and follow-up data were recorded. Results: Our study results showed no significant difference in the number of patient admission, age, and sex of patients, burn agents and length of hospital stay before and after the COVID-19 outbreak. Conclusions: Burn centers can work safely in COVID-19 outbreak, paying special attention to precautions mandated by the national and global health authorities. However, the increase in pandemic burden may force the burn centers to be converted into alternate COVID-19 facilities. In such cases, the care of burn patients may pose a great problem.